2016
DOI: 10.1039/c5an01996f
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-responsive molecular recognition chromatography using phenylalanine and tryptophan derived polymer modified silica beads

Abstract: Temperature-responsive polymers incorporating molecular-recognition sites were developed as stationary phases for high-performance liquid chromatography (HPLC). The grafted stationary phases consisted of functional copolymers composed of N-isopropylacrylamide (NIPAAm) and N-acryloyl aromatic amino acid methyl esters, i.e., phenylalanine and tryptophan methyl esters (Phe-OMe and Trp-OMe). Three novel temperature-responsive polymers, P(NIPAAm-co-Phe-OMe5), P(NIPAAm-co-Phe-OMe10), and P(NIPAAm-co-Trp-OMe5), were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 27 publications
(32 reference statements)
2
25
0
Order By: Relevance
“…Table 1 summarizes the polymer characterization data. The molecular weights and LCSTs determined in this study corresponded well with those reported previously [16]. These results indicated that the objective polymers were successfully synthesized.…”
Section: Temperature Response Of Pnipaam Copolymerssupporting
confidence: 79%
See 2 more Smart Citations
“…Table 1 summarizes the polymer characterization data. The molecular weights and LCSTs determined in this study corresponded well with those reported previously [16]. These results indicated that the objective polymers were successfully synthesized.…”
Section: Temperature Response Of Pnipaam Copolymerssupporting
confidence: 79%
“…For example, using n-butyl methacrylate (BMA) as a hydrophobic comonomer leads to increased hydrophobicity [8]. Recently, Hiruta et al reported that aromatic amino acids like L-phenylalanine and L-tryptophan were introduced to PNIPAAm as a comonomer and a new separation mode featuring molecular recognition was successfully introduced to the stationary phase, due to π-π interactions and hydrogen bonding [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selectivity of all phase was increased with decrease of temperature. The selectivity of Sil-ODA 10 was enhanced below 40 • C, which was closed to the phase transition temperature, 38 • C (Figure 3). On the other hand, for Sil-ODA 10 -AT 1 and Sil-ODA 5 -AT 5 , the enhancement of their selectivities was observed in the higher range than 40 • C. This suggests due to higher phase transition temperature (44 and 46 • C, respectively, Figure 3) than Sil-ODA 10 .…”
Section: Hplcmentioning
confidence: 99%
“…Surface modification with a copolymer system is another important issue for the preparation of materials with tailor-made properties that are composed of two different monomers having diverse chemical and/or physical properties [4][5][6]. Inorganic carrier particles with polymeric/copolymeric phases on their surface have long been used as the stationary phase for HPLC [7][8][9][10][11] because such tailor-made surface properties directly influence the retention and separation efficiency. However, molecular ordering of copolymeric phases results in supramolecular functionality.…”
Section: Introductionmentioning
confidence: 99%